Design of hypermedia: a search for the better comprehension about this theme - Freire, Luciana (InfoDesign, 2010)
Moura, Mônica. Design de Hipermídia: dos princípios aos elementos. São Paulo: NMD; Rosari, 2007. 117p. [ISBN: 978-85-88343-55-9] Besides the importance of propose discussions which are, for many time, wished by the informational designer’s, the e-book “Design de Hipermídia” highlights one innovative proposal in the presentation of its contents and also in the approach of the theme hipermedia’s design. The text is directed principally to students and professionals of this area, considering the premise that “one designer must be attentive to everything around him, exercising infinitively his sensibility, creativity and capacity of experimentation; what doesn’t means the inexistence of one method” (Moura, 2007).